GENERASI MUDA DALAM MENCARI JATI DIRI DI ERA DIGITAL: MENEMUKAN IDENTITAS SEJATI DALAM KRISTUSMELALUI PEMURIDAN - Purba, Gomgom; Steven (JURNAL TABGHA, 2025)
This study aims to explore discipleship in the younger generation finding their true identity in Christ in today's digital era. Using a qualitative approach with a case study method, this study involved young people and young adults who are active in church communities. In this case, the younger generation in searching for identity in the digital era, finding true identity in Christ through discipleship requires the development of a discipleship approach that is responsive to complex social and digital dynamics. By integrating technology and interactive learning methods, discipleship can increase the relevance and effectiveness of programs offered to the younger generation. Through proper guidance, discipleship not only helps individuals recognize their identity in faith but also equips them with the skills and beliefs to contribute positively to society. The results of the study indicate that discipleship functions as a process of spiritual learning and in-depth character building, which strengthens the values ​​of love, sacrifice, and commitment to the teachings of Christ. Through interactions in discipleship groups, young people are empowered to share hopes and challenges, strengthen a sense of solidarity, and discuss issues that are relevant to their lives. Thus, discipleship becomes a vital tool in forming a strong identity and guiding young people towards a meaningful life in line with their calling of faith.